Early Advanced Weight-Bearing After Periarticular Fractures: A Randomized Trial Comparing Antigravity Treadmill Therapy Versus Standard of Care. (January 2022) - Stinner, Daniel J.; Rivera, Jessica C.; Smith, Christopher S.; Weiss, David B.; Hymes, Robert A.; Matuszewski, Paul E.; Gary, Joshua L.; Morshed, Saam; Schmidt, Andrew H.; Wilken, Jason M.; Archer, Kristin R.; Bailey, Lane; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Summary: In current clinical practice, weight-bearing is typically restricted for up to 12 weeks after definitive fixation of lower extremity periarticular fractures. However, muscle atrophy resulting from restricting weight-bearing has a deleterious effect on bone healing and overall limb function. Antigravity treadmill therapy may improve recovery by allowing patients to safely load the limb during therapy, thereby reducing the negative consequences of prolonged non–weight-bearing while avoiding complications associated with premature return to full weight-bearing. This article describes a multicenter randomized controlled trial comparing outcomes after a 10-week antigravity treadmill therapy program versus standard of care in adult patients with periarticular fractures of the knee and distal tibia. The primary hypothesis is that, compared with patients receiving standard of care, patients receiving antigravity treadmill therapy will report better function 6 months after definitive treatment.